Early Pancreas Transplant Improves Motor Nerve Conduction in Alloxan-Induced Diabetic Rats - Spadella, C. T.; Lucchesi, A. N.; Alberti, S.; Resende, L.A. L. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The purpose of this study was to assess the temporal relationship between pancreas transplant and the development of electrophysiological changes in the sciatic and caudal nerves of alloxan-induced diabetic rats. Nerve conduction studies were performed in diabetic rats subjected to pancreas transplantation at 4, 12, and 24 weeks after diabetes onset, using non-diabetic and untreated diabetic rats as controls. Nerve conduction data were significantly altered in untreated diabetic control rats up to 48 weeks of follow-up in all time points. Rats subjected to pancreas transplantation up to 4 and 12 weeks after diabetes onset had significantly increased motor nerve conduction velocity with improvement of wave amplitude, distal latency, and temporal dispersion of compound muscle action potential in all follow-up periods (P<0.05); these parameters remained abnormal when pancreas transplantation were performed late at 24 weeks. Our results suggest that early pancreas transplant (at 4–12 weeks) may be effective in controlling diabetic neuropathy in this in vivo model.
Keywords: Diabetes mellitus; peripheral diabetic neuropathy; nerve conduction studies